(Re-)Shaping Italian-Canadian and Indigenous Connections through Naming Practices - Mongibello, Anna (Italian Canadiana, 2022)
Long before the formation of the first Italian communities in Canada, notable Italian navigators played a key role in the so-called “discovery of the Americas.” Suffice it to think of names like Cristoforo Colombo and Giovanni Caboto, who sailed to North America in 1492 and 1497 as part of European exploration journeys to the “new world.” The history of colonization in Canada and North America in general is therefore inextricably linked to these names, although Italian responsibilities in the occupation of Canada are not always acknowledged as such. On the contrary, celebratory traces of this history are still visible in the names of streets, squares, lakes, rivers, mountains, etc., as well as in public holidays and commemorative monuments. The present article aims at addressing the power of names in the creation of cultural memory. More specifically, the article explores the role that place-names and other commemorative practices linked to the Italian presence in Canada play in the commemoration of the colonial past and in the production of a narrative that celebrates the Italian contribution to its colonial occupation. Naming places, people, or holidays is not just a matter of choosing one name over another, but it reveals ideological stances and narratives. Similarly, the presence of celebratory monuments turning Caboto and Colombo into national myths and symbols of Italian Canadians ends up affecting the relationships between local Italian-Canadian communities and Indigenous peoples. Possible alternatives may change attitudes towards Indigenous peoples, thus promoting a new solidarity with the Italian-Canadian communities across the country.